LONG-TERM CONSEQUENCES OF INTERPERSONAL VIOLENCE AGAINST CHILDREN IN SPORT. Issue 4 (1st February 2017) - Vertommen, Tine; Kampen, Jarl; Veldhoven, Nicolette Schipper-van; Eede, Filip Van Den
Abstract : Background: A recent prevalence study in the Netherlands and Belgium showed that 38% of children in sport experienced psychological violence, 11% physical violence, and 14% sexual violence. Ethnic minority, lesbian/gay/bisexual (LGB) and disabled athletes, and those competing at the international level reported significantly more experiences with interpersonal violence in sport. Objective: While general literature has repeatedly shown that exposure to interpersonal violence in childhood is associated with adverse psychological outcomes in adulthood, this relationship has not yet been demonstrated in athletes. This study aims to explore the long-term consequences of these experiences on adult psychopathology and quality of life. Design: A cross-sectional, retrospective design, using an online survey, provides a prevalence estimate of interpersonal violence in sport in a representative sample of adults, prescreened on having participated in organized sport before the age of 18 ( N=4043 ). In this sample, psychopathology (depression, anxiety and somatic problems) was assessed using the Brief Symptom Inventory. Quality of life was measured with the World Health Organization Quality of Life questionnaire (WHOQOL BREF). Using Poisson and ordinal logistic regression, the impact on psychopathology and quality of life was investigated, while controlling for demographics, as well as disability, sexual orientation and adverse childhood experiences outside sport. Results: Moderate and severe experiences with interpersonal violence in sport (psychological, physical and sexual) proved to have a significant negative impact on psychopathology and quality of life in adulthood. Conclusions: This study shows that interpersonal violence against children in sport is related to mental health problems and lower quality of life in adulthood. With its Consensus Statement on non-accidental violence in sport, the IOC gives a strong impetus to prioritize athlete welfare and implement prevention policies. Sport medicine practitioners can actively contribute to a safer sports climate by being attentive to signs of violence against athletes and effectively respond to disclosures.